Interaction of music and emotional stimuli in modulating working memory in macaque monkeys. Issue 7 (27th June 2019) - Zarei, Shahab A.; Sheibani, Vahid; Mansouri, Farshad A.
Abstract: Background music is one of the most frequently encountered contextual factors that affect cognitive and emotional functions in humans. However, it is still unclear whether music induces similar effects in nonhuman primates. Answering this question might bring insight to the long‐lasting question regarding the ability of nonhuman primates in perceiving and dissociating music from other nonmusical acoustic information. In the present study, macaque monkeys were trained to perform a working memory task that required matching visual stimuli. These stimuli had different emotional content (neutral, negative, and positive). Monkeys performed the task within different background acoustic conditions (music, same‐intensity noise, and silence). We hypothesized that the auditory stimuli might interact with emotional information of visual stimuli and modulate monkeys' performance. Furthermore, if the effects of music and noise on monkeys' behavioral measures differ it would mean that monkeys perceived and processed music differently. We found that, monkeys committed more errors and were slower when they encountered stimuli with negative or positive emotional content. In the presence of music, the influence of emotional stimuli on monkeys' performance significantly differed from those of the neutral stimuli, however, in the presence of noise, the effects of emotional stimuli on monkeys' performance were not distinguishable. The dissociable effects of music and noise on monkeys' performance show that the effects of emotional stimuli were dependent on the background acoustic conditions. Our findings indicate that background music and the same‐intensity noise were differentially perceived by monkeys and influenced their cognitive functions. Abstract : The interaction between music and emotion factors on monkeys' response time. The effects of emotional stimuli on monkeys' behavior were dependent on the background acoustic information. Highlight: 1. The effects of background acoustic conditions (music, same‐intensity noise, and silence) and visual stimuli with emotional content (neutral, positive, and negative) on monkeys' performance in a working memory task were examined. 2. Monkeys committed more errors and were slower when they matched stimuli with positive or negative emotional content. 3. The effects of emotional stimuli on monkeys' performance were significantly attenuated in the presence of noise. However, in the presence of music, the effects of emotional stimuli on monkeys' performance significantly differed from those of the neutral stimuli. 4. Our findings provide evidence of distinguished effects of auditory stimuli on monkeys' cognition depending on rhythms and harmonies that humans perceive and categorize as music.